Numerical Simulation to Investigate the Effect of Adding a Fixed Blade to a Magnus Wind Turbine - Dyusembaeva, A.; Tanasheva, N.; Tussypbayeva, A.; Bakhtybekova, A.; Kutumova, Zh.; Kyzdarbekova, Sh.; Mukhamedrakhim, A. (Energies, 2024)
The investigation of aerodynamics and the establishment of flow patterns around finitelength cylinders with various end shapes in a free, boundless air flow with longitudinal and transverse flow over a wide range of geometric and regime parameters is sketchy and does not have a wide range of geometric and regime parameters. This, in turn, affects the entire aerodynamics of the streamlined body. This paper considers the numerical simulation of a wind turbine made of combined blades. CFD (computational fluid dynamics) methods based on the realisable k-ε turbulence model were used in the study. The results on the influence of the position of the fixed blade on the angle of inclination are obtained (0◦, 15◦, 30◦, 45◦, and 60◦). The authors found that the pressure of a fixed blade at an optimal angle increases the power coefficient Cp by 35–40%. The dependence of the Cp power coefficient on the rotational speed (speed coefficient) for a three-bladed wind turbine was also established, and it was determined that the maximum value of Cp = 0.28 at Z = 4.9. Based on the results obtained, it was determined that the wind turbine has a maximum power coefficient at an angle of inclination of 0 degrees.
Keywords: wind turbine; fixed blade; magnus; numerical simulation; cylinder